The Food4Years Ageing Network: Improving foods and diets as a strategy for supporting quality of life, independence and healthspan in older adults. Issue 1 (31st January 2023) - Clegg, Miriam E.; Methven, Lisa; Lanham‐New, Susan A.; Green, Mark A.; Duggal, Niharika A.; Hetherington, Marion M.
Abstract: By 2050, it is predicted that one in four people in the United Kingdom will be aged 65 years and over. Increases in lifespan are not always translated into years spent in good health. Incidence rates for chronic diseases are increasing, with treatments allowing people to live longer with their disease. There is good evidence to support changes to lifestyle to maintain or improve body composition, cognitive health, musculoskeletal health, immune function and vascular health in older adults. Much research has been done in this area, which has produced significant support for foods and nutrients that contribute to improved healthspan. Yet two major barriers remain: firstly, older adult consumers are not meeting current UK recommendations for macro‐ and micronutrients that could benefit health and quality of life and secondly, the UK‐specific recommendations may not be sufficient to support the ageing population, particularly for nutrients with key physiological roles. More work is needed to improve intakes of specific foods, diets and nutrients by older adults, through a variety of mechanisms including (i) development of specific food products; (ii) improved clarity of information and (iii) appropriate marketing, and policy changes to enable incentives. The Food4Years Ageing Network aims to build a wide‐reaching and multidisciplinary community that is committed to the development, integration and communication of healthy, affordable foods and specific diets for all older adults across the UK food landscape. The Network will identify evidence‐based strategies for improving food intake and nutrition in older adults, paving the way to "living well while living longer."